Buckling control of composite beam with piezoelectric materials - Lu, Fan. (2008)
Buckling control of laminate beams by means of piezoelectric layers bonded to the outer surfaces of the beams is studied in this project. Structures made of fiber-reinforced laminated composite materials are usually thin and flexible. When they are under in-plane compressive loading, buckling will happen. Buckling control is investigated through the use of induced strain actuators associated with the piezoelectric effect. By controlling the direction of voltage applied on each actuator, it is possible to drive the actuators in a bending deformation and provide moment to the beam. The moment can keep the beam in a straight shape and counterbalance the compressive load.